Ecological and faunistic survey of the true bugs of the infraorder Pentatomomorpha (Hemiptera) in the urban cenoses of Kharkiv City (Ukraine) - I. A. Fedyay; T. Y. Markina; A. V. Putchkov (Biosystems Diversity, 2018)
A total of 63 species of true bugs in 53 genera and 11 families of the infraorder Pentatomomorpha was recorded from the city of Kharkiv. For one species, Carpocoris purpureipennis (Pentatomidae), we obtained the first record from Left-Bank Ukraine. Formerly, this species was known from Western and Central Ukraine only. Four species of the family Lygaeidae (Nysius ericae, Perithrechus geniculatus, P. gracilicornis, Taphropeltus contractus) are new to Kharkiv Region. The families Lygaeidae (23 species of 19 genera, 38.3% of the total collected bugs), Pentatomidae (16 species of 14 genera, 26.7%), Rhopalidae (7 species of 5 genera, 11.7%), and Coreidae (6 species of 6 genera, about 3%) were the most rich in species and individual numbers. The families of Berytidae, Cydnidae and Scutelleridae were represented by two species each (3.3% out of the total collected bugs). Six species (Myrmus miriformis, Lygaeus equestris, Scolopostethus pictus, Aelia acuminata, Graphosoma lineatum, and Pyrrhocoris apterus) were abundant, eight species common, 14 species rare, and 32 species belonged to occasional elements of the urban cenoses. The true bug species composition and individual abundance were the highest in the suburban meadows and large city parks (44 and 27 species, respectively). By contrast, only seven species were registered in the green areas of the city centre (lawns, public gardens). Faunal similarity (Jaccard / Chekanovsky-Sørensen indices) of the true bug assemblages was the lowest when comparing public gardens of the city centre with the habitats of the suburbs and city parks (0.04–0.06 / 0.07–0.12), and the highest between the meadows and urban parks with glades and grassy vegetation under low recreational pressure (0.52 / 0.68). Jaccard similarity indices for the other six pairs of compared urban cenoses were low (0.1‒0.42). The average Pentatomomorpha similarity in different urban cenoses was also low (Jaccard index 0.27, Chekanovsky-Sørensen index 0.39). The essential faunal differences can be explained by both the low number of most Pentatomomorpha species and their ecological peculiarities. The proportions of various ecological groups of bugs in different urban cenoses were analyzed and discussed. Major differences were observed in the species habitat distributions while the lesser differences concerned trophic groups and hygropreferences of most species. Hortobiont and herpetohortobiont polyphytophagous species dominated all the habitats.